2023
DOI: 10.3390/f14040733
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Resilience Assessment of Rural Landscapes in the Context of Karst Rocky Desertification Control: A Case Study of Fanhua Village in Guizhou Province

Abstract: The ecological rehabilitation project has greatly curbed the serious problem of karst rocky desertification (KRD) in southern China and significantly changed the ecological environment and landscape pattern of the karst rocky desertification control areas (KRDCA). As one of the most important social–ecological fragile areas in the world, rural landscapes in KRDCA still show a strong sensitivity to disturbance. To reduce risks and improve the resilience of landscapes, this paper constructs a framework for asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…According to the classification standard of the rocky desertification intensity grade in karst areas, Xiong et al. (2002) divided the rocky desertification grade into six grades (Table 1). The three study areas were classified as follows: Huajiang (moderate to severe rocky desertification), Bijie (light to moderate rocky desertification), and Shibing (without potential rocky desertification) (Xiong et al., 2002).…”
Section: Methodsmentioning
confidence: 99%
“…According to the classification standard of the rocky desertification intensity grade in karst areas, Xiong et al. (2002) divided the rocky desertification grade into six grades (Table 1). The three study areas were classified as follows: Huajiang (moderate to severe rocky desertification), Bijie (light to moderate rocky desertification), and Shibing (without potential rocky desertification) (Xiong et al., 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Landscape Restoration in Desertification Control, Current Regional Forests and Rural Landscapes Are Found to Have High Fragility and Weak Anti-Interference Abilities, Providing a Reference for Landscape Planning and the Layout of Environmental Protection Karst areas have high landscape fragility and weak anti-interference ability. Therefore, a framework for evaluating rural landscape restoration was constructed from the perspectives of ecology, engineering, and socio-culture, and the constraints of disaster resistance and village cultural values were analyzed [15]. A multi-dimensional plan for the transformation and adjustment of village ecosystem structure to promote the restoration of landscape elasticity and the improvement of production functions was proposed.…”
Section: Through Research On the Reconstruction Of Ecological Landsca...mentioning
confidence: 99%
“…Previous research results have only qualitatively analyzed the impact of a series of ecological restoration policies, such as returning farmland to forests, immigration and relocation, and promoting the development of the forestry industry. Integrating GIS and RS technologies to quantitatively analyze the driving factors of ecosystem changes has become a trend [15,16]. Therefore, further research is needed on the impact of landscape functional zoning, population migration, and rural cultural decline on ecosystem changes.…”
Section: The Key Scientific Issues In Constructing a Framework For Ru...mentioning
confidence: 99%
“…Desertification has long been a major economic, social, and environmental issue of concern to many countries and regions of the world (Oldroyd and Leyser, 2020). Karst desertification, which is similar to desertified landscapes, has attracted much attention from the international community (Xiong et al, 2002). It has been shown that the establishment of artificial grasslands is an important initiative to rapidly repair the damaged ecological environment of rocky desertification (Wang et al, 2019), which is of great significance to promote ecological reconstruction and economic development (Fang et al, 2018;Xin et al, 2020;Bai and Cotrufo, 2022).…”
Section: Introductionmentioning
confidence: 99%